MAIN STRATEGIES OF METAPHOR TRANSLATION IN TRANSLATOLOGY - Balayan Gayane Vladimirovna (Journal of new century innovations, 2023)
Abstract: Metaphors are an inseparable part of every language, which are found in large numbers in most languages. Since the meaning metaphors cannot be understood from the surface meanings of the individual words that make up them, there are some problems in the processes of understanding and translation. This article is devoted to the study main strategies of metaphor translation discussed by popular scholars.